Glial cells as drug targets: What does it take?. Issue 10 (28th April 2016) - Möller, Thomas; Boddeke, Hendrikus W. G. M.
Abstract : The last two decades have brought a significant increase in our understanding of glial biology and glial contribution to CNS disease. Yet, despite the fact that glial cells make up the majority of CNS cells, no drug specifically targeting glial cells is on the market. Given the long development times of CNS drugs, on average over 12 years, this is not completely surprising. However, there is increasing interest from academia and industry to exploit glial targets to develop drugs for the benefit of patients with currently limited or no therapeutic options. CNS drug development has a high attrition rate and has encountered many challenges. It seems unlikely that developing drugs against glial targets would be any less demanding. However, the knowledge generated in traditional CNS drug discovery teaches valuable lessons, which could enable the glial community to accelerate the cycle time from basic discovery to drug development. In this review we will discuss steps necessary to bring a "glial target idea" to a clinical development program. GLIA 2016;64:1742–1754 Main points: Glial cell‐ based targets receive increased attention in drug development. What makes a good drug target. Steps and pitfalls for preclinical drug development.